INTEGRATING AI CHATBOTS (CHATGPT/GEMINI) TO IMPROVE STUDENTS' WRITING SKILLS IN COMPOSING RECOUNT TEXTS - Destia Herlisya; Yohana Puspita Dewi; Purna Wiratno (Institute of Research Institutions and Community Service (LPPMP) of STKIP PGRI Bandar Lampung, 2026)
This research describes the improvement of students' writing skills in composing recount texts through AI Chatbots (ChatGPT/Gemini). The study used Classroom Action Research (CAR) at SMA Adiguna Bandar Lampung. Data were collected through classroom observations and writing tests over two cycles. Quantitative data indicate that AI chatbots improve students' English writing skills and learning engagement. In the first cycle, the students' learning activities showed a mean score of 67.00 (less active), which increased to 75.25 (quite active) in the second cycle, with an 8.25-point improvement. Students' writing performance improved from a pre-cycle mean score of 67.00 (19% of students met mastery criteria) to 69.00 in Cycle I (30% mastery), and 77.25 in Cycle II (60% mastery). These findings suggest that AI Chatbots enhance students' motivation and technical proficiency in writing recount texts.